2023
DOI: 10.1177/1420326x231153922
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of light environment perception, eye movement and physiology in university professional classroom based on virtual reality experiment

Abstract: In this study, virtual reality technology was used to simulate the virtual scene of three common light environment forms of professional classrooms in universities. The experimental results show that people’s environmental perception is related to the average pupil diameter, saccade frequency, high frequency/low frequency (LF/HF) and skin conductance change rate in a combined light environment; moreover, when the colour temperature is 4500 K, the space is brighter, more spacious, more relaxed and the willingne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…[1][2][3] Of greater significance, lighting quality could affect students' performance and well-being in both short-term and long-term, 4 which have been explored by multiple studies. [5][6][7] By comparing over 10,000 students' outcomes of the Iowa Test of Basic Skills from 71 schools, Tanner 5 found that daylight had significant effects on students' variance in Science and Reading vocabulary scores. A positive relationship was found between students' performance scores and design factors associated with daylight, including the type of window shading, percentage of window facing south, window glazing and the window-tofloor area ratio.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Of greater significance, lighting quality could affect students' performance and well-being in both short-term and long-term, 4 which have been explored by multiple studies. [5][6][7] By comparing over 10,000 students' outcomes of the Iowa Test of Basic Skills from 71 schools, Tanner 5 found that daylight had significant effects on students' variance in Science and Reading vocabulary scores. A positive relationship was found between students' performance scores and design factors associated with daylight, including the type of window shading, percentage of window facing south, window glazing and the window-tofloor area ratio.…”
Section: Introductionmentioning
confidence: 99%